Effect of nano‐porous SiNx interlayer on propagation of extended defects in semipolar (112¯2)‐orientated GaN. Issue 8 (6th March 2017) - Monavarian, Morteza; Izyumskaya, Natalia; Müller, Marcus; Metzner, Sebastian; Veit, Peter; Das, Saikat; Özgür, Ümit; Bertram, Frank; Christen, Jürgen; Morkoç, Hadis; Avrutin, Vitaliy
Abstract : Semipolar orientations of GaN have attracted considerable attention as potential platforms for high brightness light‐emitting devices. The heteroepitaxy of semipolar GaN layers results in high densities of threading dislocations (TDs) and basal‐plane stacking faults (BSFs). Various defect reduction methods have been employed to improve the crystal quality of the semipolar substrates, among which the in situ epitaxial lateral overgrowth (ELO) is of great importance due to its relatively simple procedure, low cost, and high effectiveness in reducing density of TDs. We have shown that in situ deposited nano‐porous SiN x could act as a blocking layer preventing both TDs and BSFs from penetrating to overgrown semipolar ( 11 2 ¯ 2 ) GaN layers. In this contribution, we present microscopic study of interaction of extended defects (TDs and BSFs) with nano‐porous SiN x in ( 11 2 ¯ 2 ) ‐oriented GaN layers grown by MOCVD on m‐ sapphire substrates. Cross‐sectional scanning transmission electron microscopy‐cathodoluminescence (STEM‐CL) reveals reduction of BSF density by about 50% for dual insertion of SiN x interlayers. It is also shown that the integrated CL intensity is enhanced by about two orders of magnitude indicating that the majority of TDs are blocked by the interlayers. The interaction of TDs and BSFs with nano‐porous SiN x and defect distribution in GaN nuclei are briefly discussed.